(untitled) (GYMNASIUM, 2017)
This study represents a preliminary stage of a research envisaging the creation of training programs that would use the TENNIS 10s training strategy for children between 5 and 10 years old. The aim of this study was to know the coaches’ opinion regarding the introduction of the Tennis 10s training method, using a questionnaire containing 12 questions that was applied to 28 tennis coaches. The main goals were to determine the coaches’ level of knowledge in regards to the Tennis 10s training method, and to identify the way in which the coaches learned and used this new method in achieving top athletic performances. The results of the research showed the coaches’ level of knowledge and their predisposition regarding the introduction of this new strategy in their athletes’ training, the conclusions highlighting the adherence of the majority of the coaches to that strategy.